The strategic relevance of logistics: new perspectives. Issue 1 (2016) - Göpfert, Ingrid; Stephan, Michael; Wellbrock, Wanja; Ackermann, Malte
We measure the strategic relevance of logistics in multinational corporations (MNCs) using two proxies: 1) the communication of logistics endeavours in annual reports; 2) the employment of logistics competencies on the top management level. We define logistics competencies as the employment of executive board members who are assigned to logistics tasks. We examine 360 MNCs and their annual reports of the years 2000, 2004 and 2008 using content analysis. We show that there are considerable differences in the communication efforts amongst the geographical regions and the associated industries using the standard industrial classification (SIC) scheme. We present evidence that corporations originating in Asia are more likely to employ logistics competencies at the top level than their North American and European counterparts. On the other hand, Asian corporations are much more taciturn in their corporate disclosure policy. On an industrial level the transportation and chemicals subsectors are more likely to employ logistics competencies in their executive boards than other subsectors. Additionally, using partial point-biserial correlations, we demonstrate that the employment of logistics competencies is related to higher financial performance, further substantiating the strategic relevance of logistics for MNCs.